Determinants of Foreign Direct Investment in Indonesia - Dewi, Cynthia Sari; Hutomo, Farend Olivia (Conference Series, 2021)
The objective of this research is to investigate the influence of macroeconomic factors such as market size, labor cost, interest rate, exchange rate, trade openness, and inflation to the foreign direct investment in Indonesia. This research uses a quantitative approach with time series data, quarterly from 2006 to 2019. The data is processed using SPSS Statistics 23 software, specifically linear regression analysis method and passed the classical assumption test. Results show that there is a partially significant relationship between market size, labor cost, interest rate, exchange rate, and trade openness to the foreign direct investment, meanwhile inflation does not significantly affect the foreign direct investment. These findings hopefully can help the government to make wiser policies to increase the foreign direct investment.